Analisis Kinerja Jaringan WLAN Menggunakan Metode TCBH pada SMAN 7 Luwu Utara - Umi Aulia; Syafriadi (Prosiding SISFOTEK, 2024)
This research aims to describe the network performance at SMAN 7 North Luwu. The research method used is qualitative. The qualitative method is a research study that is descriptive in nature and tends to use analysis and is more visible in the data collection processes and techniques carried out, namely observation, interviews and literature studies. Based on the results of research on network performance at SMAN 7 North Luwu from the beginning to the research stage, it can be concluded that after analyzing the network performance by implementing Qos at the agency, it was said to be quite good, but at some times it was said to be moderate due to delays in the network at SMAN 7 Luwu. North, therefore we need a system to analyze a network that emphasizes how to monitor and measure performance to see the quality of service from how much network performance on infrastructure such as upload and download speed, by measuring bandwidth, delay, packet loss, throughput and jitter parameters. by using the Axence NetTools v5 application at SMAN 7 North Luwu